2011
DOI: 10.1099/mic.0.047803-0
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the Porphyromonas gingivalis conjugative transposon CTnPg1: determination of the integration site and the genes essential for conjugal transfer

Abstract: In our previous study, extensive genomic rearrangements were found in two strains of the Gram-negative anaerobic bacterium Porphyromonas (Por.) gingivalis, and most of these rearrangements were associated with mobile genetic elements such as insertion sequences and conjugative transposons (CTns). CTnPg1, identified in Por. gingivalis strain ATCC 33277, was the first complete CTn reported for the genus Porphyromonas. In the present study, we found that CTnPg1 can be transferred from strain ATCC 33277 to another… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 39 publications
1
22
0
1
Order By: Relevance
“…The DNA sequences flanking transposon insertion sites were determined using arbitrary PCR (43,44). The genomic DNA of the transformant was isolated by the agarose block method, as previously described (45).…”
Section: Methodsmentioning
confidence: 99%
“…The DNA sequences flanking transposon insertion sites were determined using arbitrary PCR (43,44). The genomic DNA of the transformant was isolated by the agarose block method, as previously described (45).…”
Section: Methodsmentioning
confidence: 99%
“…Our results here indicate that the traA–Q locus in strain W83 is involved in low-frequency conjugal transfer of chromosomal DNA, and our previous work found that plasmids were not a substrate for the W83 transfer system (18). In contrast, the traA–Q locus in P. gingivalis ATCC 33277 can mobilize plasmids by a DNase I-insensitive mechanism, and a recent study revealed the traA–Q -containing element cTnPg1 to be capable of excision and conjugation (45); both behaviors are similar to those of conjugative Bacteroides transposons. These cTn-like elements may have been shared between the oral and intestinal Bacteroidetes populations at some time in evolutionary history, and similar loci are found in the genome sequences of other members of phylum Bacteroidetes , indicating that DNA conjugation by traA–Q is widespread in this taxonomic group.…”
Section: Discussionmentioning
confidence: 99%
“…They can excise themselves from the genome where they are integrated, transfer themselves to a recipient by conjugation and integrate into the recipient genome [39]. Thus CtnPg1, which was the first complete Ctn found in P. gingivalis , was able to excise itself from chromosomal DNA using an integrase (Int; PGN-0094) encoded in CtnPg1 and produce a circular intermediate [10].…”
Section: Introductionmentioning
confidence: 99%